Factors affecting the participation rate of higher-education students in domestic solid waste segregation (case study: Nazloo Campus of Urmia University) - Vahid Eskandari; Mehdi Ghanbarzadeh Lak (علوم محیطی)
Introduction: Encouraging higher-education students, as ambassadors of environmental activities within their homes, to increase their participation in waste segregation of recyclables, can provide a clear perspective for the proper management of wastes in the country. Most of the previous studies on identifying the factors affecting public participation rate in the segregation of wastes have focused on urban areas (and not on educational environments such as universities), and the effects of the interaction of various factors on the results have not been considered. Accordingly, in this research, the level of knowledge, type of attitude, and methods of increasing the participation rate of students in waste segregation have been investigated in the Nazlou campus of Urmia University. Material and methods: A total of 113 questionnaires containing 11 multi-part questions were randomly distributed among the students (face to face interview) and the results were analyzed by SPSS software. The validity of the mentioned questionnaire was assessed by the face validity technique and its reliability was evaluated based on Cronbach's Alpha Coefficient (i.e., 0.884). For descriptive purposes, frequency distribution tables were used. For inferential purposes, the relationship between the variables of each hypothesis was obtained by Chi-square test. Furthermore, using Kramer's and Kendal's coefficient of correlation, the relationship between independent and dependent variables was assessed. Using Mann-Whitney test tables, the severity of the correlation coefficients were determined separately. Results and discussion: The test results of the hypotheses showed that factors including knowledge level and gender of interviewees play a significant role in the student’s participation. On the other hand, due to the limited age range of the target population and their high level of education, these factors didn’t have much impact on the responsible behavior of the academics. Preferring educational methods such as organizing exhibitions on recyclable products by interviewees, and no impact of face-to-face education, indicated that they are willing to acquire related information through new educational methods. Interviewees asserted that being certain about the expenditure of project revenues on students’ welfare affairs is the main factor in the increase in their participation rate. In other words, because environmental measures are newly developed and social activists have limited experiences, the participation of individuals in waste segregation activities without fulfilling their financial expectations is not feasible. Conclusion: The results of the current study indicated that most students of Nazloo Campus of Urmia University were willing to participate in domestic waste segregation (with a score of 7.56 out of 9). Unfortunately, due to their inadequate knowledge about the subject (with a score of 4.54), and lack of associated executive programs in the university (with a score of 1.96), as well as the lack of training programs provided by the university (with a score of 2.71), the waste segregation was not implemented properly. Due to the poor evaluation of the university staff’s performance in the field of providing waste segregation educations, the students had no trust in the university and this fact had a significant effect on their participation in the plan.